Development of High Quality Human Resources Through Qur'anic Spiritual Intelligence at SMAIT Ash-Shohwah Berau, East Kalimantan - Nurul Hidayah; Tobroni Tobroni; Khozin Khozin; Abdul Haris (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2025)
This study aims to explore the concept of Qur’anic Spiritual Intelligence and its role in developing high-quality human resources, with a specific focus on the implementation at SMAIT Ash-Shohwah Berau. Qur’anic Spiritual Intelligence refers to a form of spiritual capacity derived from deep interaction with the Qur’an, encompassing the intelligence of the spirit, soul, heart, and moral consciousness. This research employs a qualitative method with a case study approach to provide an in-depth understanding of the phenomenon. Data were collected through semi-structured interviews with teachers and students, participant observations during religious and academic activities, and documentation analysis of school programs. The findings reveal that the cultivation of Qur’anic Spiritual Intelligence at SMAIT Ash-Shohwah Berau is systematically integrated into the school’s curriculum and extracurricular programs, particularly through the high-quality Tahfidzul Qur’an program, which is mandatory for all students. The process of memorizing the Qur’an is not only aimed at achieving mastery of verses but also at nurturing closeness to Allah SWT, shaping attitudes and values that form the foundation of high-quality human resources. Students participating in the program demonstrate notable improvements in discipline, responsibility, enthusiasm for learning, social competence, emotional regulation, honesty, independence, and leadership skills. Furthermore, the study highlights that Qur’anic Spiritual Intelligence serves as a transformative element, influencing both academic achievement and personal character. It fosters an integrated development that balances intellectual capability with moral integrity, enabling students to contribute meaningfully to society. The results suggest that embedding Qur’anic Spiritual Intelligence in educational settings can be a strategic pathway for producing graduates who are not only academically competent but also spiritually grounded and socially responsible. This has significant implications for Islamic education institutions aiming to develop comprehensive human resources aligned with Qur’anic values and the demands of the modern world.